2023
DOI: 10.1038/s41467-023-38469-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to air pollution and severe COVID-19 in Catalonia: a population-based cohort study

Abstract: The association between long-term exposure to ambient air pollutants and severe COVID-19 is uncertain. We followed 4,660,502 adults from the general population in 2020 in Catalonia, Spain. Cox proportional models were fit to evaluate the association between annual averages of PM2.5, NO2, BC, and O3 at each participant’s residential address and severe COVID-19. Higher exposure to PM2.5, NO2, and BC was associated with an increased risk of COVID-19 hospitalization, ICU admission, death, and hospital length of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We addressed this concern in previous work and found that the overall uncertainty in attributable burden calculations, expressed by the 95% confidence intervals (of order 35%), is much more strongly determined by the relative risk calculations than by the resolution of the analysis. 42 Finally, air pollution was shown to contribute to deaths from covid-19, 43 44 estimated at a proportion of about 15% globally, 45 but this additional health burden does not apply to the estimates for 2019.…”
Section: Discussionmentioning
confidence: 99%
“…We addressed this concern in previous work and found that the overall uncertainty in attributable burden calculations, expressed by the 95% confidence intervals (of order 35%), is much more strongly determined by the relative risk calculations than by the resolution of the analysis. 42 Finally, air pollution was shown to contribute to deaths from covid-19, 43 44 estimated at a proportion of about 15% globally, 45 but this additional health burden does not apply to the estimates for 2019.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate about the association between air pollution, SARS-CoV-2 infection, and COVID-19 severity. While the study of this relationship is complex (59), several potential biological mechanisms underpinning these associations have been identified, ranging from air pollution's influence on the transport and viability of viral particles to its impact on the body's innate defense mechanisms and long-term immune function (60)(61)(62).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Therefore, the present multicenter research aimed to evaluate the association between exposure to air pollution (PM 10, PM 2.5 , and B(a)P levels) estimated during the viral incubation period and further clinical course of COVID‐19 in patients hospitalized in Poland during two pandemic waves dominated by different variants of SARS‐CoV‐2. In this regard, assessed exposure had to be considered short‐term, contrary to other studies in which air quality data taken into account corresponded to annual or longer intervals 33–36 . Specifically, we examined the relationship between increased levels of air pollutants and early COVID‐19 symptoms, the concentration of inflammatory and coagulopathy markers at admission, oxygen saturation, the need for oxygen supplementation and mechanical ventilation, and fatal outcome.…”
Section: Introductionmentioning
confidence: 99%